Investigating the Relationship between Goal Orientation and Academic Status in Students of Abadan University of Medical Sciences in 2022-2023 - Jamshid Bahmaei; Bagher Pahlavanzadeh; Zahra Abdolahi Arpanahi; Ebrahim Kharazinejad; Maryam Jafarpourian (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Goal orientation is one of the determining variables in the quality of the learning process and academic progress of people. Therefore, this study was designed and implemented to investigate the relationship between goal orientation and academic achievement among the students of Abadan University of Medical Sciences, Abadan, Iran. Methods: The present study was a descriptive-analytical correlational research that was conducted cross-sectionally in 2022-2023. The sampling method was stratified and clustered. The study sample consisted of 259 students from Abadan University of Medical Sciences. The data collection tool was the Academic Goal Orientation Questionnaire of Buffard et al. (1998), and the students' grade point average (GPA) in the last semester was used as the measure of their academic status. Data were analyzed using SPSS 26 and AMOS 24 software. Results: The average age of the students was 24.3 (±2.4) years and their average last semester GPA was 16.57 (±1.25). The average score of the failure avoidance component was 20.32 (± 4.11), performance 14.08 (± 5.58), and goal-mastery 9.43 (± 3.82). The correlation coefficient showed that although there was a positive relationship between goal orientation components and academic achievement, it was not significant. The correlation coefficient also showed that the academic semester had a positive and significant relationship with the components of performance orientation and mastery orientation; however, it had a negative relationship with failure avoidance. Conclusion: According to the results of this study, no significant relationship was found between the three components of goal orientation and academic achievement. It can be suggested that educational planners provide and improve educational conditions in such a way that students move towards mastery and performance goals and move away from avoidance orientation.